Aspects of rare earth element enrichment in Allegheny Plateau coals, Pennsylvania, USA. (January 2022) - Hower, James C.; Eble, Cortland F.; Xie, Panpan; Liu, Jingjing; Fu, Biao; Hood, Madison M.
Abstract: The Allegheny Plateau in western Pennsylvania, western Maryland, and northern West Virginia has relatively flat-lying strata with southwest-northeast-trending anticlines cored by splay faults originating from the thrust faults and southeast-northwest-trending lineaments. The lineaments define both the structural relief of the anticlines and the coal rank. Coal rank in the Pennsylvanian Allegheny Group coals is medium volatile bituminous in the region of less-prominent structural relief and low volatile bituminous in the region with more pronounced anticlines. Zinc and Cl exhibit high values in coals in the vicinity of the lineaments. Although coal rank was not a parameter in the Principal components analysis, the highest rank coals clustered together in a quadrant defined, in part, by the Zn concentration. Zinc was selected as a parameter due to its possible link with hydrothermal mineralization and Zr and TiO2 /Al2 O3 were selected based on their presumed association with detrital mineral influences. The highest rare earths + Y values in benches of the Lower Kittanning coal were found at sites close to the lineaments. Negative or negligible Ce anomalies (δCe) and strongly positive Gd anomalies (δGd) suggest marine or hydrothermal influences and negative Eu anomalies (δEu) along with high TiO2 /Al2 O3 values suggest a terrestrial input. The plots of δCe vs. δGd and δCe vs. δEu show that the low volatile bituminous coals are segregated from the other coals, suggesting that the factors that influenced coal rank also influenced the distribution of the rare earth elements. Highlights: The Allegheny Front is the eastern region of the Northern Appalachian coalfields. For this work, the focus was on the region to the east of the Chestnut Ridge anticline. Pottsville, Allegheny, and Conemaugh formation coals were examined. High concentrations of Zn and Cl in coals were associated with cross-strike lineaments. Coal rank and rare earth emplacement may have been mutually controlled.